Difluoromethanesulfonyl hypervalent iodonium ylides for electrophilic difluoromethylthiolation reactions under copper catalysis - Arimori, Sadayuki; Matsubara, Okiya; Takada, Masahiro; Shiro, Motoo; Shibata, Norio (Royal Society open science, 2016)
Difluoromethanesulfonyl hypervalent iodonium ylides 2 were developed as electrophilic difluoromethylthiolation reagents for a wide range of nucleophiles. Enamines, indoles, β-keto esters, silyl enol ethers and pyrroles were effectively reacted with 2 affording desired difluoromethylthio (SCF2H)-substituted compounds in good to high yields under copper catalysis. The reaction of allyl alcohols with 2 under the same conditions provided difluoromethylsulfinyl (S(O)CF2H) products in good yields. The difluoromethylthiolation of enamines is particularly effective with wide generality, thus the enamine method was nicely extended to the synthesis of a series of difluoromethythiolated cyclic and acyclic β-keto esters, 1,3-diketones, pyrazole and pyrimidine derivatives by a consecutive, two-step one-pot reaction using 2.